The Teacher's Role in Applying the Hadith Release Method in SDIT Cendekia Pematangsiantar District - Ali Imran Sinaga; Farida Jaya; Andi Prahara Hasibuan (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The research objectives were to determine: (1) the role of the teacher in the implementation of memorizing hadith in SDIT Cendekia, (2) the method applied by the teacher in memorizing hadith at SDIT Cendekia and (3) the impact obtained by students from the application of memorizing hadith in SDIT Cendekia. The research method used is qualitative. Data collection is done by observation and interviews. The research findings show: (1) the role of the teacher is as a facilitator, motivator, and the most important role in memorizing this hadith is to instill good morals to students who are in accordance with the guidance and behavior of the prophet through habituation. (2) the method applied by the teacher in memorizing hadiths used the oral method and movement, they did this on the basis of the age of grade 1-2, they were still not very fluent in reading hadith and were still not very fluent in reciting it, while for grades 3-6 the method was used. The tasalsuli thariqah, the jam'i thariqah method and the muqassam thariqah method. and, (3) the impact that students get from the application of memorizing hadiths is positive things that are felt by students, teachers and parents, including students' morals and actions that are more focused, students know and love the prophet more, students can find out the existing morals. in the Prophet's self, students remember each other friends if their actions are not in accordance with the hadith of the prophet they learned, and always try to behave according to the hadith of the prophet.